An Environmental and Life Study of Retithrips Syriacus Mayet Thripidae: Thysanopter in Babylon (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Laboratary and field studies conducted  in the province of Babylon which is 60 km away from Baghdad on Retithrips Syriacus Mayet during the year 2015-2016, as well as, the percentage of infection in the different varites of grapes  of this insect . The results showed :- The class summer Royal, variety was the most favorable of grapes to Thrips throughout the numbers of the adults which were settling down more than the other  varsity Prinster, which was the least preferable one to Trips .-The highest rate was recorded to the adults of the R. syriacus which existed on the grapes trees was in October, November, reached to 5.00 adult/leaf of some trees which have already been composted by an organic compost rated 5ml/L and 4.08 adults/leaf to some other trees also been composted by an organic compost within 10 lm/L percentage successfully , while, the highest rate to the Thrips larvae's existence was through September and October. Whilst, 4.16 larva/leafto some composted trees by an organic compost in the rate of 5 M/L and 9.00 larva/leaf also to some composted trees, by an organic compost, its percentage was 10 M/L successfully . Yet, in January it reached the least rate to be found. For March 0.00 adult or larva/leaf.- Trips adults were more attracted to the yellow traps recorded 18.83 percentage of the number of insects were settling down and 0.00 insect/ trap for the white one.- The highest average was recorded  to the existence of the Thrips adults on grapes trees was in December and January to reach 15.55 and 44.75 adult/leaf successfully, yet, for the larvae's existence, the highest average was in September and January as 110.19 and 157.77 larva/leaf alike. The least rate for its existence in March, April, May to reach 0.00 adult or larva/leaf . Concerning the locations which some samples were taken from, the samples of the botanical part, showed out the highest destiny to the adults and larvae, reached 18.16, 58.73 adult or larva/plant successfully in the upper part of the plant. Yet, the percentage was less to the existence of the Thrips' adults and larvae came to 5.39, 20.84 adult or larva/plant successfully than the lower part of the plant.